BULLYING E CYBERBULLYING NOS CURRÍCULOS DE REFERÊNCIA DOS ESTADOS BRASILEIROS: CONFLITOS E VIOLÊNCIAS SOB A PERSPECTIVA DAS POLÍTICAS EDUCACIONAIS - MIRIAM PINHEIRO BITENCURTI RÜZGAR (2023)
Bullying is considered “systematic intimidation” by Law nº 13.185/2015 and article. 5 determines the duty of educational establishments to combat bullying hence its unequivocal articulation with the curriculum. The objective of this research was to investigate whether the Reference Curriculum of the Federative Units of Brazil (RCFUB) contemplates the themes of bullying and cyberbullying, how these themes are treated in the curriculum and if the proposals present in the curriculum are implemented through actions, projects and programs, that is, they constitute educational policies. This documentary research, with a qualitative approach (Lüdke; André, 2020), had three stages: bibliographical, exploratory and analysis of results. The theoretical bases of the research covered the works of Saviani (2015; 2016; 2019; 2021), Libâneo, Oliveira e Toschi (2018) and Gramsci (2007), compatible with the adopted method, historical-dialectical materialism. The time frame of the study covered the period from 2016 to 2022, as compliance with the legislation came into effect in 2016 and the BNCC was under construction. The study was directed to elementary schools, since the author works in this segment and noticed the increase in cases of bullying/cyberbullying over time, mainly, during the pandemic (COVID-19) that started in 2020, when students who had internet access increased the amount of time using their electronic devices, both for entertainment and for school study, which varied between synchronous, asynchronous or hybrid. For the analysis, Bardin's Content Analysis (2016) was used. The bibliographical part allowed us to identify that most students had already witnessed violence at school, including bullying and cyberbullying. Of the works analyzed (51), most (43.1%) investigated the identification of the presence of bullying/cyberbullying at school, 37.3% investigated interventions to combat school bullying/cyberbullying. Of the one hundred and seven state laws from several different secretariats (health, safety, social assistance, and culture) found with the word bullying, ninety-four involve the school to combat it. In relation to the RCFUB, all of them contemplate bullying and cyberbullying in some way and explicitly contain the words bullying/cyberbullying or with the expression of a culture of peace. In all RCFUB, in Religious Education, competence six contains the expression culture of peace, but this component is optional registration, which means that not everyone will have access to this information. The research reveals that there are laws to combat bullying and it is present in curricula. It shows that when it is worked on, discussions, debates, dialogues and interviews are most often used. It was concluded that the ongoing curriculum policy, centered on skills and abilities and which takes socio-emotional skills as the privileged means to combat bullying/cyberbullying, proves to be inefficient because it does not consider social, cultural, economic and political aspects. The more people are aware of brutal inequalities, the less will be the perception that the fight against bullying lies in the mere identification and punishment of aggressors.